Rapid scan experiments using a conventional FT-ICR mass spectrometer - G. Parisod; T. Gäumann (CHIMIA)
This paper reports results obtained with a home-made FT-ICR spectrometer when it is run in the rapid scan mode described by McIver. The ability of the technique for the measurements of wide range mass spectra has been demonstrated.